BIO421: Plant Biology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2022)
This course is designed to provide students with principle of plant classification, fundamental of plant physiology, growth and development. The plant tissue culture and plant genetic manipulation will also be highlighted.